Get the lead out! [lead free solder]. - Trumble, B.
Concern over lead's toxicity launched a quest for alternatives to the tin-lead solder common in printed-circuit board manufacture. The options for no-lead solders rely on tin as the base metal with smaller amounts of other metals, such as antimony, bismuth, copper, indium, silver, or zinc, added to enhance performance. Tin, which is considered to be one of the least toxic metals, will most probably endure as the base metal since it is relatively inexpensive, sufficiently available, and possesses desirable physical properties. In considering alternatives, the cost and availability of metals also come into play. Indeed, the limited availability and high costs of indium, bismuth, and silver-based alloy systems will likely prevent their widespread use. In 1997, a tin-copper alloy was used to assemble a desktop telephone, the first such product made with lead-free solder
Keywords: Sn-Cu.; Antimony; Availability; Bismuth; Copper; Cost; Desktop telephone; Indium; Lead free solder; Printed-circuit board manufacture; Silver; Tin-copper alloy; Zinc